Intrahepatic TH17/TReg Cells in Homeostasis and Disease—It’s All About the Balance - Drescher, Hannah K.; Bartsch, Lea M.; Weiskirchen, Sabine; Weiskirchen, Ralf (Frontiers in Pharmacology, 2020)
Acute and chronic hepatic inflammation subsequently leading to liver fibrosis and end-stage liver disease is believed to be the consequence of an imbalance of the TH1/TH2 cell response. More recently, a new CD4+ T helper cell subset was discovered mainly characterized by the production of IL-17 and IL-22. Initially, these TH17 cells were found to be predominantly involved in the host defense against infections and in autoimmune diseases. Extensive studies over the past 10 years revealed that the development of TH17 cells favors pro-inflammatory responses in almost all tissues and that a reciprocal relationship between TH17 and TReg cells exists. This balance between TH17and TReg cells is critical for immune reactions especially in injured liver tissue and the recovery to immune homeostasis. The pathogenic contribution of TH17 and TReg cells in autoimmunity, acute infection and chronic liver injury is divers and varies in different disease etiologies. Understanding the mechanisms which promote TH17 cell development, recruitment and maintenance and at the same time suppress TReg cells is crucial for potential new therapeutic strategies in liver diseases. Active manipulation of the balance between pathogenic and regulatory processes in the liver is thought to allow the focused restoration of homeostasis especially during hepatic inflammation.